Vomiting in a toddler – An unsuspected cause - Rashmi, N; Yerrapragada, Devesh Bhaskar; Kumar, M G Anil (Indian Journal of Child Health, 2021)
Vomiting in young children can be due to a varied etiology ranging from gastritis, urinary tract infection, and metabolic problems to serious life-threatening conditions such as myocarditis, intracranial space occupying lesions, and acute surgical conditions such as intussusception, malrotation, and torsion testis. However, intractable vomiting in a toddler as presented here was due to an unexpected cause as the history was not initially forthcoming for the same. Here, we presented the case of a 21-month-old girl who was admitted with vomiting and low-grade fever, initially suspected to have viral fever/urinary tract infection. All relevant investigations were within normal limits, ruling out metabolic causes. However, on day 3, she showed features of intestinal obstruction for which imaging was done which revealed a mass in the distal ileum, and she was taken up for immediate laparotomy and the ileal mass was excised, which turned out to be a foreign body, that is, three rubber balls. The child recovered completely post-surgery and was discharged three days later. Hence, the lessons learnt from this case would be that, there is no short cut to detailed history taking and meticulous clinical examination; using imaging at the appropriate time helps in timely intervention and life-saving management.